Neuroscience, Education and Metal Health - Arboccó de los Heros, Manuel (2016)
The following article presents a series of investigations, reflections, and quotes about neuroscience, education, and psychology. Each area is specialized in some matters but at some point they share territory and mutually benefit one another, and help us to increasingly understand the complex world of learning, the brain, and human behavior. We hope them to be of interest and a promoter of new thoughts.